Kinetic Studies of Co-Pyrolysis of Rubber Seed Shell with High Density Polyethylene - Chin, Bridgid; Yusup, S.; Al Shoaibi, A.; Kannan, P.; Srinivasakannan, C.; Sulaiman, S. (Elsevier, 2014)
This paper investigates the thermal degradation behavior of rubber seed shell (RSS), high density polyethylene (HDPE), and the HDPE/RSS mixtures (0.2:0.8 weight ratio) using thermogravimetric analyzer under non-isothermal condition in argon atmosphere at flowrate of 100 ml min−1. Cellulose, hemicellulose, and lignin are also analyzed in this study for comparison of pyrolysis behavior with RSS. The experiments were conducted at different heating rates of 10, 20, 30, and 50 K min−1 in the temperature range of 323–1173 K. The kinetic data is generated based on first order rate of reaction. It is observed that the thermal degradation behavior of the main components in biomass such as hemicellulose, cellulose, and lignin differs during pyrolysis process due to the structural differences that leads to distinctive pathways of degradation of feedstock. It is found that there are one, two, and three stages of decomposition occurring in HDPE, RSS, and HDPE/RSS mixtures respectively during the pyrolysis process. The remaining solid residue increases with an increase in heating rate regardless of the type of samples used. The activation energies (EA) for RSS, HDPE, HDPE/RSS mixtures are 46.94–63.21, 242.13–278.14, and 49.14–83.11 kJ mol−1 respectively for the range of heating rate studied.